Settlement between the offender and the victim according to the criminal code of Serbia - Ćorović Emir (Temida, 2011)
The Criminal Code of the Republic of Serbia from 2005 (which went into effect on January 1st, 2006) has envisaged a particular basis for remittance of punishment which had been unknown in our criminal law. It is about settlement between the offender and the victim, an institution reflecting ideas of restorative justice. Although the settlement between the offender and the victim offers great possibilities, it has not received enough attention in our criminal law literature. We usually come across perfunctory elaboration of the matter, which is justified by insufficient regulations. Thus numerous questions and dilemmas related to the implementation of this institution are being opened, so we will try to give answers to these questions in this paper, that is, to give some solutions for the dilemmas, relying on the positive law of the Republic of Serbia.